Pengaruh Kepercayaan Diri Dan Citra Pemimpin Terhadap Kekaguman Bawahan Pada Kepemimpinan Transformasional (Studi Pada Pegawai Pemerintah Daerah Propinsi Diy) - Linawati Linawati; Sofiati Sofiati (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2019)
This research is intended to analyze the influence the leader’s self-assurance and the leader’s image on the awe of employee based on syncretical model of charismatic/ transformational leadership. The respondents consist of 78 government employees of Regional Province of Yogyakarta. Questionnaire are used to collect data from the respondents and the instrument of questionnaire from Behling and McFillen are used to measures the variable of self-assurance, image and awe. The data were analized by Multiple Regression Analysis. The result of the study indicate that: (i). the leader’s self-assurance has no significant influence on the awe of employee, (ii). the leader’s image has significant influence on the awe of employee.